Usage-based studies in modern Hebrew background, morpho-lexicon, and syntax - Berman, Ruth Aronson; Dattner, Elitzur; Grossman, Eitan; Nir, Bracha; Reshef, Yael (Studies in language companion series,, 2019)
"The goal of the volume is to shed fresh light on Modern Hebrew from perspectives aimed at readers interested in the domains of general linguistics, typology, and Semitic studies. Starting with chapters that provide background information on the evolution and sociolinguistic setting of the language, the bulk of the book is devoted to usage-based studies of the morphology, lexicon, and syntax of current Hebrew. Based primarily on original analyses of authentic spoken and online materials, these studies reflect varied theoretical frames-of-reference that are largely model-neutral in approach. To this end, the book presents a functionally motivated, dynamic approach to actual usage, rather than providing strictly structuralist or formal characterizations of particular linguistic systems. Such a perspective is particularly important in the case of a language undergoing accelerated processes of change, in which the gap between prescriptive dictates of the Hebrew Language Establishment and the actual usage of educated, literate but non-expert speaker-writers of current Hebrew is constantly on the rise"--